The story of “aestexts”: About developing a concept and exploring it as a tool in a research process about the kindergarten's soundscapes - Engesnes, Nina (Nordic Journal of Art & Research, 2023)
This article explores how "aestexts" can be created and create meaning in a practice-led research process on exploring the kindergarten’s soundscapes. By ‘aestexts’ is meant texts with aesthetic qualities, often in different modalities, that serve as tools in research both in individual thought processes and in reflexive collaborative processes. The aestexts act as ’tools of thought‘ in the exploration of researcher roles, as empirical data together with photographs and transcribed group conversations, and as examples of analysis. A/r/tography, poetic inquiry and narrative analysis are used as methodological approaches. In the article, the reader can follow the development of the aestexts from being verbal, poetic renderings to also encompassing auditory and visual narratives. Through this change, the aestext also goes from acting as a tool in exploring one’s own research role to having significance as a co-creative research tool in a research group. The’work also shows that aestexts can lend themselves to express complexity and subjective experiences including the evocative and that the kindergarten’s soundscapes emerge with several nuances. The texts are further explored as knowledge resources in practice-led research in close cooperation between the kindergarten sector and early childhood education. Webpage photo: "Lyttelinjer" by Tona Gulpinar